The digital innovation playbook creating a transformative customer experience - Webb, Nicholas J., 1958- (Wiley, 2011)
"The first half The Digital Media Innovation Playbook provides comprehensive case examples of how organizations both large and small have deployed Real Open methodologies to grow both sales and profit. The case examples will include well-known companies like Word Press, Autodesk, Cisco, just to name a few (30-50 Fortune 500 and startups that rule the digital space in all). Case examples will cover a wide range of markets, including medical and biotechnologies, consumer product companies, industrial firms, service organizations, research and universities. The first half of the book lays down empirical evidentiary support to prove the benefits of these methods. The second part provides a step-by-step game plan that will allow any organization to apply these methods and achieve immediate results. The chapters will be broken down by the step-by-step process that is driven by a variety of tools that can be used to fit the unique needs of each organization. As part of the value added benefits of this book, a wide range of online free resources will be available with the proof of purchase of the book"--